Study of hedonistic lifestyles based on sexes and cultural background (students of batak and minang culture) - Ristra Sandra Ritonga; Muhammad Fadlil; Agung Tri Prasetia; Muhammad Rifat Affani (Jurnal Aplikasi IPTEK Indonesia, 2018)
This research aims at investigating the varieties of hedonistic lifestyles adopted by university students based on their sexes and cultural backgrounds. Culture is referred to in this research is the culture of Batak and Minang culture. The formulation to the problem for this research is there any difference in the lifestyle of hedonism in terms of gender and culture. This research method using descriptive quantitative. Sample for this study where students numbered 80 people. Data collection techniques in this study using questionnaires about the behavior of hedonism. Data were analyzed using t-test. Based on testing and data analysis significance level of <0.005. Namely, the hedonistic lifestyle in terms of gender has the significance of 0.000, and the lifestyle of hedonism in terms of culture has a significance of 0.005. This means that there are differences in terms hedonistic lifestyle of sex and Minang and Batak culture at the level of students.